Antibacterial Potential of Endophytic Fungi from Avicennia marina Against Pathogenic Bacteria Methicillin Resistant Staphylococcus aureus and Pseudomonas aeruginosa - Mulyani, Yeni; Dewi, Annastasya Asti; Annisa, Nanda; Khaerunnisa, Nur Asmi; Sautraja, Gerardo Gaudentius; Aziz, Adrians Maulana; Pangkerego, Aziz Aprian (Jurnal Biologi Tropis, 2026)
Antibiotic resistance has become a global health concern, driving the search for new antibacterial sources. Owing to their ability to biosynthesize diverse bioactive secondary metabolites, endophytic fungi isolated from mangrove plants have emerged as a sustainable resource for natural antibacterial compounds. This study aimed to evaluate the antibacterial activity of endophytic fungi isolated from Avicennia marina collected from the Nusawiru Mangrove Conservation Area, Pangandaran, Indonesia. Isolation was performed using the direct plating method on Potato Dextrose Agar (PDA), followed by purification to obtain six pure isolates. The isolates were screened for antibacterial activity against Methicillin-Resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa using an agar plug diffusion assay. Among the six isolates obtained, only AVM BT 4.2 exhibited antibacterial activity against MRSA, producing total inhibition zones of 15.77 ± 1.51 mm at 24 h and 15.39 ± 0.73 mm at 48 h, categorized as strong inhibition. However, none of the isolates inhibited P. aeruginosa. These findings indicate the potential of A. marina endophytic fungi as a source of antibacterial compounds against resistant bacteria and support further studies on molecular identification and bioactive metabolite characterization of secondary metabolites from the active isolates to support the development of natural antibiotic candidates based on sustainable coastal biological resources.